Two new species of Tamarixia (Hymenoptera: Eulophidae) from Chile and Australia, established as biological control agents of invasive psyllids (Hemiptera: Calophyidae, Triozidae) in California - Zuparko, Robert L.; de Queiroz, Dalva Luiz; la Salle, John (Zootaxa, 2011)
Tamarixia schina Zuparko sp. nov. and T. dahlsteni Zuparko sp. nov. are described. Both species have become established in California following their introductions from Chile and Australia, respectively, for control of invasive psyllids. Tamarixia schina is known from Calophya schini (Hemiptera: Calophyidae) on Schinus molle (Anacardiaceae) and T. dahlsteni from Trioza eugeniae (Hemiptera: Triozidae) on Syzygium paniculatum (Myrtaceae). The use of Tamarixia in biological control is discussed, and an annotated list of world species including distribution, hosts, and host plants, is provided. Tetrastichus atamiensis Ashmead is transferred to Tamarixia as Tamarixia atamiensis (Ashmead) comb. n.